2012
DOI: 10.1158/1535-7163.mct-11-0659
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Metronomic Oral Dosing of a Prodrug of Gemcitabine (LY2334737) Causes Antitumor Effects in the Absence of Inhibition of Systemic Vasculogenesis

Abstract: Metronomic chemotherapy refers to the close, regular administration of conventional chemotherapy drugs at relatively low minimally toxic doses with no prolonged break periods; it is now showing encouraging results in various phase II clinical trials, and is currently undergoing phase III trial evaluation. It is thought to cause anti-tumor effects primarily by antiangiogenic mechanisms, both locally by targeting endothelial cells of the tumor neovasculature and systemically by effects on bone marrow derived cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 37 publications
3
41
0
1
Order By: Relevance
“…Although these natural products have been shown to be highly effective in clinical trials (29), some drugs such as vinblastine and paclitaxel can produce drug resistance (30), and other drugs such as vincristine, produce a strong cytotoxic effect (31). It has also been reported that treatment with topotecan, a water-soluble derivative of camptothecin, caused immunologic suppression in breast cancer (LM2-4) xenografts (32). Therefore, the identification of safer and more effective drugs from natural medical plants for breast cancer metastasis is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Although these natural products have been shown to be highly effective in clinical trials (29), some drugs such as vinblastine and paclitaxel can produce drug resistance (30), and other drugs such as vincristine, produce a strong cytotoxic effect (31). It has also been reported that treatment with topotecan, a water-soluble derivative of camptothecin, caused immunologic suppression in breast cancer (LM2-4) xenografts (32). Therefore, the identification of safer and more effective drugs from natural medical plants for breast cancer metastasis is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LY2334737, an orally bioavailable prodrug of gemcitabine, exhibited antitumor effects in preclinical models of ovarian and breast cancer when administered in metronomic doses. 35 In the current study, the design of GnRH-gemcitabine conjugates was based on improving the therapeutic potential of gemcitabine as follows: 1) Reduction of gemcitabine's metabolic inactivation. It has been shown that gemcitabine prodrugs can be designed specifically to affect its interaction with cytidine deaminase, the enzyme responsible for gemcitabine's poor pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…When metronomically dosed orally once a day for 14 days in the human colon HCT-116 xenograft model, LY2334737 showed excellent antitumor activity that is equivalent to standard high doses of gemcitabine.HCl typically administered intraperitoneally (9). Orthotopic models of human metastatic breast LM2-and ovarian SK-OV-3 cancers also responded well to LY2334737 treatment (16).…”
Section: Introductionmentioning
confidence: 99%
“…"Metronomic dosing" refers to administration of chemotherapy at frequent intervals (e.g., daily) with low, minimally toxic doses (13). In contrast to intravenous delivery of maximally tolerated doses of chemotherapeutic agents, advantages include: (i) direct, continual tumor growth inhibition and (ii) an indirect effect through inhibition of angiogenesis and vasculogenesis (13)(14)(15) or, as shown for LY2334737, increased tumor blood flow thereby potentially enhancing drug delivery (16). When metronomically dosed orally once a day for 14 days in the human colon HCT-116 xenograft model, LY2334737 showed excellent antitumor activity that is equivalent to standard high doses of gemcitabine.HCl typically administered intraperitoneally (9).…”
Section: Introductionmentioning
confidence: 99%